2021
DOI: 10.1016/j.psj.2020.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin prevents insulin resistance, hepatic inflammation, and activates autophagy associated with high-fat diet–induced fatty liver hemorrhagic syndrome in aged laying hens

Abstract: The aim of this study was to investigate the effects of osteocalcin ( OCN ) on fatty liver hemorrhagic syndrome ( FLHS ) in aged laying hens. Thirty 68-week-old White Plymouth laying hens were randomly assigned into conventional single-bird cages, and the cages were randomly allocated into one of 3 treatments (n = 10): normal diet (ND + vehicle, ND + V ), high-fat diet (HFD + vehicle, HFD + V ), and HFD + OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…High-fat diets can cause fatty liver hemorrhagic syndrome in animals [ 67 ]. Plasma AST and ALP are used as indicators to reflect liver damage [ 68 ], and high levels lead to liver damage [ 69 ]. Previous studies reported that ALP showed a positive correlation with PUFA in milk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-fat diets can cause fatty liver hemorrhagic syndrome in animals [ 67 ]. Plasma AST and ALP are used as indicators to reflect liver damage [ 68 ], and high levels lead to liver damage [ 69 ]. Previous studies reported that ALP showed a positive correlation with PUFA in milk [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the secretion of insulin was obviously increased. After intervention with exogenous OCN in mice fed with high fat and high glucose, the fat thickness of mice was decreased, but the insulin secretion and sensitivity were increased [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, OCN may regulate energy metabolism and have endocrine activity [16,20,21]. After intervention with exogenous OCN, the fat thickness of mice fed with high fat and high glucose was decreased, but the insulin secretion and sensitivity were increased [22][23][24][25]. Previous study showed that OCN treatment improved glucose homeostasis and lipid metabolism [26].…”
Section: Introductionmentioning
confidence: 99%
“…The pathological mechanisms of fatty liver in chickens are similar to nonalcoholic fatty liver disease (NAFLD), including insulin resistance, inflammation, and liver oxidative stress [ 23 ]. The multiple-hit pathogenesis theory considered that long-term hepatic fat accumulation can produce lipotoxicity, resulting in impairment of hepatocyte function and reduction of antioxidant capacity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%